A Corrosion Suppression Coatings for Molten Nitrate Salt - Sarah Yasir; Indrat Aria; Chris Sansom (SolarPACES Conference Proceedings)
The use of solar energy for power generation provides an efficient sustainable energy solution. Among a number of technologies developed for power generation using solar energy, concentrating solar power (CSP) is encouraging because it makes use of mature technology in the power block. Thermal energy storage (TES) is added to CSP, making it competitive with other power generation technologies and delivering dispatchable energy. Molten salts are one of the materials of choice for the TES. Although the use of molten salts as heat transfer fluid and thermal storage in CSP has various advantages, storage tanks and pipework can be highly susceptible to corrosion. Different approaches have been adopted to suppress corrosion including the use of specialised alloys and high purity molten salts; however, both contribute to a substantial increase in construction and operating costs.